History of SMAN 3 Painan as the First Boarding School in Pesisir Selatan (2011-2024) - Indra, Zul; Najmi, Najmi (HISTORIA: Jurnal Program Studi Pendidikan Sejarah, 2025)
This research examines the history of SMAN 3 Painan as the first boarding school in Pesisir Selatan during the 2011-2024 period. SMAN 3 Painan implements an educational model where students live in dormitories for 24 hours, following an integrated educational program. This study uses historical methods, including heuristics, source criticism, interpretation, and historiography. Primary sources were obtained from government archives and interviews, while secondary sources came from books and journals. The results show that the establishment of SMAN 3 Painan began after the junior high school competency test results in West Sumatra in 2008, where Pesisir Selatan ranked second. The school was built to accommodate high-achieving students to ensure they continued studying in their home region. Since its founding, SMAN 3 Painan has achieved various national-level accomplishments.